Putative predictive biomarkers of survival in patients with metastatic pancreatic adenocarcinoma treated with gemcitabine and ganitumab, an IGF1R inhibitor - McCaffery, Ian; Tudor, Yanyan; Deng, Hongjie; Tang, Rui; Suzuki, Samuel; Badola, Sunita; Kindler, Hedy L; Fuchs, Charles S; Loh, Elwyn; Patterson, Scott D; Chen, Li; Gansert, Jennifer L (Clinical cancer research, 2013)
This planned exploratory analysis assessed the predictive nature of baseline circulating factors of the insulin-like growth factor (IGF) axis on the treatment effect of ganitumab (monoclonal antibody inhibitor of IGF-1 receptor) plus gemcitabine in a randomized phase II study in metastatic pancreatic adenocarcinoma. Baseline levels of IGFs/IGF binding proteins (IGFBP) were analyzed in serum or plasma. Mutations and gene expression were analyzed in archival samples. Treatment effects between biomarker subgroups were compared for overall survival (OS). Associations of tumor markers with OS were evaluated. For patients with evaluable samples, ganitumab was associated with improved OS versus placebo (HR, 0.49; 95% CI: 0.28-0.87). The treatment effect on improved OS was strong in the patient subset with higher levels of IGF-1, IGF-2, or IGFBP-3, or lower levels of IGFBP-2, but not so on the other corresponding subset. Median OS of ganitumab versus placebo in patients with higher levels of IGF-1, IGF-2, and IGFBP-3 was 16 versus 6.8 months (HR, 0.25; 95% CI: 0.09-0.67), 16 versus 5.9 months (HR, 0.24; 95% CI: 0.09-0.68), and 16 versus 6.8 months (HR, 0.28; 95% CI: 0.11-0.73), and in patients with lower IGFBP-2 levels was 12.7 versus 6.6 months (HR, 0.19; 95% CI: 0.07-0.55). Interaction between treatment and IGFs/IGFBPs in multivariate analyses suggested predictive potential for IGF-2 (P = 0.002) and IGFBP-2 (P = 0.02). KRAS mutation status and PTEN expression were not associated with OS. Baseline circulating factors of the IGF axis may predict OS benefit from ganitumab plus gemcitabine in metastatic pancreatic adenocarcinoma.